2016
DOI: 10.1534/g3.116.035881
|View full text |Cite
|
Sign up to set email alerts
|

Little White Lies: Pericarp Color Provides Insights into the Origins and Evolution of Southeast Asian Weedy Rice

Abstract: Weedy rice is a conspecific form of cultivated rice (Oryza sativa L.) that infests rice fields and results in severe crop losses. Weed strains in different world regions appear to have originated multiple times from different domesticated and/or wild rice progenitors. In the case of Malaysian weedy rice, a multiple-origin model has been proposed based on neutral markers and analyses of domestication genes for hull color and seed shattering. Here, we examined variation in pericarp (bran) color and its molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 46 publications
3
41
0
Order By: Relevance
“…Because rice is a genomic model species with a well‐annotated reference genome and molecularly well‐characterized domestication genes, evidence for such adaptive introgression can be explicitly examined using dense, genome‐wide SNP markers (Hufford et al., ). This genome‐wide approach can serve as a useful complement to recent candidate gene studies which have suggested adaptive introgression of wild rice alleles conferring shattering ( sh4 , Song et al., ) and seed dormancy ( Rc , Cui et al., ) in some Malaysian weedy rice strains.…”
Section: Introductionmentioning
confidence: 99%
“…Because rice is a genomic model species with a well‐annotated reference genome and molecularly well‐characterized domestication genes, evidence for such adaptive introgression can be explicitly examined using dense, genome‐wide SNP markers (Hufford et al., ). This genome‐wide approach can serve as a useful complement to recent candidate gene studies which have suggested adaptive introgression of wild rice alleles conferring shattering ( sh4 , Song et al., ) and seed dormancy ( Rc , Cui et al., ) in some Malaysian weedy rice strains.…”
Section: Introductionmentioning
confidence: 99%
“…For such traits, introgression from wild populations rather than crop varieties could be adaptive for allowing the weeds to persist and proliferate in agricultural fields. Comparisons of the distributions of crop versus wild alleles at multiple domestication genes can thus provide insights on patterns of adaptive introgression into weed populations from domesticated and wild relatives (Song et al 2014;Cui et al 2016;Huang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Comparative analyses of domestication genes and neutral markers have proved particularly insightful in evolutionary studies of weedy rice (Song et al 2014;Cui et al 2016;Huang et al 2018). These analyses have largely relied on 3 well-characterized rice domestication genes: sh4 (controlling loss of shattering in the crop), Rc (controlling loss of pericarp pigmentation and seed dormancy in the crop), and Bh4 (controlling loss of dark-pigmented hulls in the crop).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations